ASSESSMENT OF YOUTH PERCEPTION TOWARDS POLICE: A REVIEW - Shahriza Ilyana Ramli; Nadhrah A. Kadir (Journal of Islamic, Social, Economics and Development, 2023)
Youth perception on police is crucial since they are future leader of the society. Despite the significant of the issue, there is a little review paper found. Hence, this paper will be looking into the youth perspective on police. It was motivated by the belief that the perception on police in a massive pedagogy that needs to scrutinize perspective of its context. The goal of this review is to synthesize literature from 2017 to 2022 on the context of youth perception on police using ATLAS.ti 8. 24 article journals from four databases namely Scopus, Web of Science, Science Direct and Emerald Insight are taken in analyzing the current trend of the issue and vectors involved. Throughout the analysis, ethnic has been identified as the main vector to the issue, followed by other factors; procedural justice which is referred to personal experiences, media and other demographic profile elements. The results benefit future study as it can be a guideline for enhancing perception on police.